Synthesis, Crystal Structure and Fungicidal Activity of Novel 1,5-Diaryl-3-benzoyloxy-1H-pyrazoles - Liu, Yuan-Yuan; Li, Yi; Zhu, Hong-Jun; Chen, Kai; Huang, Bin; Yang, Ya-Ping (Asian Journal of Chemistry, 2014)
Seven novel 1,5-diaryl-3-benzoyloxy-1H-pyrazoles (2a-2g) were prepared by the DCC condensation of 1,5-diaryl-1H-pyrazol-3-ols (1a-1g) with benzoic acid. Their structures were characterized by elemental analysis, IR, 1H NMR and mass spectral data. The structure of 5-(3,4-dimethoxyphenyl)-1-phenyl-3-benzoyloxy-1H-pyrazole (2d) was also determined by single crystal X-ray diffraction analysis. Bioassay results indicated that the compounds 5-(4-fluorophenyl)-1-phenyl-3-benzoyloxy-1H-pyrazole (2f) and 1,5-diphenyl-3-benzoyloxy-1H-pyrazole (2a) exhibited excellent-to-medium fungicidal activity against Sclerotinia sclerotiorum at a dosage of 10 μg/mL. The structure-activity relationships (SAR) were also discussed